Cartographic model of the spatial change of soil by sub-basins in Texcoco, Estado de Mexico: 1977-2000 - Escalona Maurice, Miguel J.; Jiménez Moreno, María Josefa; Sancho Comíns, José (Revista Mexicana de Ciencias Agrícolas, 2017)
In this research, Landsat satellite images of the 1977 year  MSS, 1989 TM and 2000 ETM were used to analyze the  morphological and functional status of the sub-basins  landscape of the Texcoco municipality. In the municipality  there are seven sub-basins and two divisions of water  between the Mexico Basin and the section corresponding  to the Puebla-Tlaxcala Basin. The analysis indicates that  six sub-basins showed drastic changes in relation to the  vegetation type, grassland, scrubland and forest, and in  the agricultural surface under irrigation and rainfed. The  Manzano River subbasin in the study period maintains a  relative equilibrium because it does not show changes in  the natural vegetation surfaces and productive areas. Based  on data El Tejocote-Santa Mónica subbasin is considered  as an area with no alteration in its land use.
Keywords: change of land occupation, satellite images, information systems